Perubahan kandungan fruktosa, glukosa dan sukrosa selama perkembangan buah apel manalagi=The Change of Fructose, Glucose and Sucrose Contents during Development of Apple Cultivar Manalagi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT This research was carried out to study the change of fructose, glucose and sucrose contents during development of apple cultivar rnianalagi, with the objectives to get information for determination of optimal picking time. Fruits were pecked eight times with an interval of one week, starting from 79 to 128 days after fruit sets. Detemination of sugars were performed by high performance liquid chromatography. â¢ Results showed that fructose increases as the maturity increases from 86 days and then decreases from 121 days after fruit sets. Both glucose and fructose start increasing at 93 days after fruit sets. Although the increase of sucrose continued up to 128 days, however, glucose contents seemed to decrease again at 121 days after fruit sets.